Seawater desalination utilising waste heat by low-temperature evaporation. (20th November 2007) - Raha, A.; Srivastava, A.; Rao, I.S.; Majumdar, M.; Srivastava, V.K.; Tewari, P.K.
Utilisation of waste heat is one of the ecofriendly ways to produce low-cost desalted water. Keeping this in mind, Low-Temperature Evaporation (LTE) desalination technology utilising low-quality waste heat in the form of hot water (as low as 50?C) or low-pressure steam (0.13 bar) has been developed to produce high-purity water (conductivity <2 ?S/cm) directly from seawater. LTE technology has found major applications in nuclear reactors to produce high-quality desalted water for make-up water requirements. Continuous and successful operation of a 30 Te/day LTE desalination plant utilising waste heat from the CIRUS nuclear research reactor has demonstrated the safety, reliability, exceptional plant availability and economics of nuclear desalination by LTE technology. Utilisation of waste heat from the Main Heat Transport (MHT) purification circuit of an Advanced Heavy Water Reactor (AHWR) to produce about 250 Te/day of high-quality desalinated water is also proposed. Recently, we have commissioned a 50 Te/day two-effect low-temperature desalination plant with cooling tower where the specific energy and cooling water requirements are significantly reduced. This paper discusses the salient features of the LTE desalination plant, its applications and advantages.